Depression and quality of life among patients with hematological cancer in a Malaysian hospital - Das, Priscilla; Awang, Hamidin; Md. Zain, Azhar; Naing, Khin Ohnmar@Noor Jan; Md Said, Salmiah; Khalid, Bahariah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2011)
Objective: To determine the prevalence of major depressive disorder (MDD) in hematological cancer patients and to investigate MDD with quality of life. Methods: The research, which uses a cross sectional design, has been carried out at Ampang Hospital, Kuala Lumpur. The hospital is a tertiary referral center for cancer cases that include non-Hodgkin lymphoma, acute myelogenous leukemia, acute lymphoblastic leukemia, Hodgkin lymphoma and other hematological cancers. In total, 105 patients with hematological malignancies were included in the study. This study employed the MINI International Neuropsychiatric Interview for diagnosis of MDD, the Patient Health Questionnaire (PHQ-9) for symptom severity of depression and the European Organisation for Research and Treatment of Cancer Quality Of Life questionnaire (EORTC QLQ-C30) to assess the quality of life of the respondents. Result: The response rate was 83.3%. The prevalence of MDD was 24.8% (n=26) with the majority of cases classified as moderately severe depression (38.5%). About 92.3% (n=24) of depressed hematological cancer patients were diagnosed with a current episode of MDD. The depressed patients also had significantly reduced quality of life in physical, role, emotional, cognitive and social domains (p<0.05). They also had significantly more symptoms of fatigue, nausea and vomiting, dyspnea, insomnia, appetite loss, constipation and diarrhea in addition to having financial difficulties and poor global health statuses (p<0.05). Conclusion: The prevalence of depression among the hematological cancer patients was high and the depressed patients had reduced qualities of life. Special attention in psychotherapy would help to improve both depression level and the quality of life in these patients.